(untitled) (Bangladesh Journal of Medical Biochemistry, 2023)
Breast cancer is the most common cancer among women in Bangladesh. About 69% cancer death of women is due to breast cancer. In Bangladesh the incidence rate of breast cancer is about 22.5 per 100000 female. Female who carries mutation in the BRCA1 gene have an 80% chance of developing breast cancer during their lifetime. Due to its high prevalence, genetic testing for BRCA1 mutation has become an integral part of clinical practice. This study was aimed to characterize the mutation at chromosome 17q21 by targeting BRCA1 gene among Bangladeshi women with familial breast cancer. This descriptive case series study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka, from July 2017 to June 2018. In this study, thirty diagnosed breast cancer patients with family history breast cancer were selected according to the selection criteria from the Department of Surgery and Department of Radiotherapy, Dhaka Medical College, Dhaka. Mutations were detected by Next Generation Sequencing method. Characterization and clinical significance were verified from NCBI genome database. The study parameters were presence of mutation, types of mutation, clinical significance, frequency (%) of mutation. In this study, sixteen distinct mutations were found. Three pathogenic mutations (10%) were found among the patients which were nonsense mutations. Pathogenic mutations were c.5251C>T, c.2158G>T and c.1059G>A. Three mutations of uncertain significance with missense variant, five benign mutations of missense variant and five benign mutations of silent variant were also found among thirty patients. In this study we found that, Bangladeshi women with familial breast cancer had 10% pathogenic mutations. Early screening for BRCA1 gene mutations might provide better information for health to those who have family history of breast cancer. Bangladesh J Med Biochem 2018; 11(2): 17-23